USE OF ERACOND BIOSTIMULATION TO INCREASE VITALITY OF MULBERRY SILKWORM - Ismatullayeva Diloram Adilovna; Umida Khaknazarova (Journal of Discoveries in Applied and Natural Science, 2023)
Thanks to the reforms carried out in the next five years, the silk industry in Uzbekistan developed rapidly, the production of silk fabric increased 4 times, the export of silk products increased 3.5 times, and the export of silk fabric increased 50 times. We can see that as a result of feeding with leaves sprinkled with Eracond biostimulation, the viability of worms was 13.4% higher in foreign hybrids than in the comparator, and 27.7% in local hybrids.